Selection of innovative mechanisms of legal support of urban planning projects in conditions of turbulence - Poltavets , Ihor (Ways to Improve Construction Efficiency, 2025)
The article explores the conceptual and applied principles of the formation of innovative mechanisms of legal support of urban planning projects in conditions of turbulent environment. Legal support is considered not only as a set of regulatory and procedural requirements, but as an adaptive, structured, changeable, hierarchical and multi-level system of legal process management, integrated into the life cycle of an urban planning project. The feasibility of the transition from the fragmented application of legal norms to a systemic approach within the framework of information support of construction objects (VIM-modeling), focused on ensuring legal stability and manageability of project activities in conditions of variability of the regulatory and institutional environment, is substantiated.Within the framework of the study, a conceptual model of legal support for urban development projects was proposed, which combines the initial legal analysis, the formation of innovative legal requirements of the customer, a legal implementation plan and adaptive legal levels of regulation. An algorithm of legal support with a correction cycle was developed, which ensures flexible response to changes in legislation, administrative practice and external factors without violating the integrity of the urban development project. Particular attention was paid to the formalization of the process of selecting and adjusting legal mechanisms in situations of uncertainty. An approach to the selection of innovative legal support mechanisms as a multi-criteria choice task in terms of linguistic description using the theory of fuzzy sets was proposed. This allows taking into account the qualitative nature of legal criteria, the subjectivity of expert assessments and the multidimensionality of legal risks. It is proven that the combination of a conceptual model, an algorithmic approach and methods of fuzzy multi-criteria analysis creates a scientific basis for increasing the effectiveness of legal support for urban development projects throughout their life cycle in a turbulent environment